ANALISIS DAN REKOMENDASI STRATEGI PENGHIDUPAN USAHA MIKRO KECIL DAN MENENGAH KOTA SALATIGA SEBELUM DAN SAAT PANDEMI COVID-19 - Rishana Shanti Y.; Mujio Mujio; Yeriko Septiawan; Janthy Trilusianthy Hidayat; Dion Achmad Armadi; Novida Waskita Ningsih; Habil Nugraha; Rindiani Agustina Rahayu; Devi Komala Sari; Mega Fernandina (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
Livelihood is defined as a stream of income or resources for everyone to be able to maintain their survival. The existence of the Covid-19 pandemic has caused changes in various sectors, one of which is the economy and especially in MSMEs. The Field Work Lecture activity conducted in Salatiga City aims to (1) describe the dynamics of MSMEs during the Covid-19 Pandemic (2) review policies related to MSMEs before and during the Covid-19 Pandemic (3) compare livelihood assets, access, and activities of MSME actors Salatiga City before and during the Covid-19 pandemic (4) reviewed the livelihood strategies of MSME actors during the Covid-19 Pandemic (5) compiled policy recommendations for MSME actors during the Covid-19 Pandemic with analysis results and field data. Field activities are carried out using primary data collected using interviews and questionnaires as well as secondary data derived from statistical data from relevant agencies and policy documents. The output of this activity is in the form of changes in assets, access, activities, and livelihood strategies as well as policy recommendations regarding MSMEs during the Covid-19 Pandemic.